Existing and alternative air pollution monitoring platforms in Nepal: A systematic review - Shrestha, Prateek Man; Bhattrai, Sudip; Darlami, Kamal; Karki, Ashish; Prajapati, Rakesh Chandra (Journal of Innovations in Engineering Education, 2023)
Air pollution has become one of the most significant threats to the well-being of humanity and the environment in many developing countries, including the Himalayan nation of Nepal. The use of both stationary and mobile instrumentation platforms for environmental and atmospheric research has witnessed a significant growth globally in the last two decades. In this review, we explore the current status of air quality monitoring infrastructure as well as a future scope of using new platforms using low-cost air sensors for pollution mapping in Nepal. While large-scale regional dynamics of air pollution in the country have been previously studied using both experimental and modeling-based approaches, usability of low-cost  instrumentation platforms in Nepal have not been explored by past studies. From the retrospective discussions regarding the past studies, we discuss here the data needs that can be fulfilled with low-cost measurements using land-based, automotive, aerial and satellite-based platforms. The importance of hyper-local air quality monitoring is highlighted in the context of Nepal, followed by the identification of recent advancements in sensor technologies, available facilities and infrastructure in Nepal.